Sex-related differences in patients with ST-segment elevation myocardial infarction - Chávez, Francisco (2020)
Objective: To determine the epidemiological characteristics, location of the infarction, type and times of reperfusion, as well as in-hospital adverse events, distributed by sex in patients with ST-segment elevation myocardial infarction (STEMI) in Peru. Methods: It is a sub-analysis of the PEruvian Registry of ST-segment Elevation Myocardial Infarction (PERSTEMI), which was an observational, prospective and multicenter study about patients over 18years-old, who were hospitalized for ST-segment elevation myocardial infarction. Epidemiological and clinical characteristics, management and in-hospital adverse events were compared according to sex. Results: 396 patients were studied, 20.9% were female, with a predominance of octogenarian populationover men. High blood pressure was the most frequent risk factor in women (74.7 Vs. 50%, p =0.001); as well as atypical clinical manifestations such as dyspnea (40.9 Vs. 27.1%, p = 0.012) and syncope (10.8 vs. 3.8%, p = 0.017). On the other hand, the inferior wall myocardial infarction was more frequent in women (51.8 vs. 38.98%). There were no significant differences regarding the reperfusion therapy used (Fibrinolysis, primary PCI, PCI in general); as well as in times of ischemia (6 vs. 5.6 hours, p = 0.456), reperfusion times and hospital stay between both sexes. However, the female sex presented higher in-hospital mortality (21.6 vs. 7%, p = 0.001), mechanical complications (8.4 vs. 1.9%, p =0.008), cardiogenic shock (15.6 vs. 9.5%, p= 0.087) and heart failure (33.7 vs. 24.9%, p = 0.072). Conclusions: STEMI in females presents at significantly older age compared to males and is associated with higher in-hospital mortality and mechanical complications.